PREVALENSI STRESS KERJA APARATUR SIPIL NEGARA (ASN) DI SEKRETARIAT DEWAN PERWAKILAN RAKYAT DAERAH (DPRD) PROVINSI BANTEN - Lalan Suhendarlan; Ipah Ema Jumiati; Rina Yulianti; Delly Maulana (Administratio, 2022)
Workers in Indonesia are vulnerable to psychological problems or emotional disorders in the form of job stress. The results of the Mercer Marsh Benefit (MMB) survey (2021), which involved more than 1,000 workers in Indonesia, found that 2 out of 5 workers experienced stress due to work. One of the workers who are at risk of experiencing job stress is the government employees (ASN) at the secretariat of the Banten regional people's representative council (abbreviated: DPRD Banten). The purpose of this study was to evaluate the prevalence of ASN job stress at the secretariat DPRD Banten, in accordance with applicable regulatory standards. This study uses a quantitative approach with descriptive analysis techniques, based on a cross-sectional study design. The results showed that the average job stress level of ASN at the secretariat DPRD Banten was 2.57. There are four categories of job stress levels experienced by ASN at the secretariat DPRD Banten, namely very low (SR), low (R), moderate (S), and high (T). The highest prevalence is a low job stress level of 45.59%. The second order is the prevalence of moderate job stress levels of 25.33%. Furthermore, the prevalence of high job stress levels is 4.5%. The smallest prevalence comes from the very low job stress category of 2.3%. The main factor that becomes a stressor is the burden of responsibilities too to themselves and others.